I swear I use no art at all : 10 years, 100 books, 18,788 pages of book design - Grootens, Joost (Rotterdam : 010 Publishers, 2010)
This book displays and dissects the career and design motives of graphic designer Joost Grootens. In a systematic fashion it charts the first 100 books designed by Grootens over the past ten years. In the first chapter, '10 years', Grootens uses timelines, lists and graphs to map the course of his career as a designer, the people he worked with and the places where the work took place. In '100 books', the designer dissects his book designs. He details the grids, formats, paper stocks, colours and typefaces, and charts the books' structures and compositions. '18,788 pages' shows at actual size a selection of spreads from books designed by Grootens, including the internationally acclaimed atlases. In the text 'I swear I use no art at all' Joost Grootens gives a personal account of making books and the ideas behind his designs.
Includes bibliographical references (p. 74-76) and index.
boek
Keywords: Grootens, Joost